Delegating Responsibility International Cooperation on Migration in the European Union - Micinski, Nicholas R. (University of Michigan Press, 2022)
Delegating Responsibility explores the politics of migration in the European Union and explains how the EU responded to the 2015-17 refugee crisis. Based on 86 interviews and fieldwork in Greece and Italy, Nicholas R. Micinski proposes a new theory of international cooperation on international migration. States approach migration policies in many ways-such as coordination, collaboration, subcontracting, and unilateralism-but which policy they choose is based on capacity and on credible partners on the ground. Micinski traces the fifty-year evolution of EU migration management, like border security and asylum policies, and shows how EU officials used "crises" as political leverage to further Europeanize migration governance. In two in-depth case studies, he explains how Italy and Greece responded to the most recent refugee crisis. He concludes with a discussion of policy recommendations regarding contemporary as well as long-term aspirations for migration management in the EU.